Influence of postural changes on haemodynamics in internal carotid artery bifurcation aneurysm using numerical methods - Raghuvir Pai Ballambat; Mohammad Zuber; Shah Mohammed Abdul Khader; Anurag Ayachit; Kamarul Arifin bin Ahmad; Rajanikanth Rao Vedula; Sevagur Ganesh Kamath; Ibrahim Lutfi Shuaib (Visual Computing for Industry, Biomedicine, and Art, 2022)
Abstract Cerebral intracranial aneurysms are serious problems that can lead to stroke, coma, and even death. The effect of blood flow on cerebral aneurysms and their relationship with rupture are unknown. In addition, postural changes and their relevance to haemodynamics of blood flow are difficult to measure in vivo using clinical imaging alone. Computational simulations investigating the detailed haemodynamics in cerebral aneurysms have been developed in recent times not only to understand the progression and rupture but also for clinical evaluation and treatment. In the present study, the haemodynamics of a patient-specific case of a large aneurysm on the left side internal carotid bifurcation (LICA) and no aneurysm on the right side internal carotid bifurcation (RICA) was investigated. The simulation of these patient-specific models using fluid–structure interaction provides a valuable comparison of flow behavior between normal and aneurysm models. The influences of postural changes were investigated during standing, sleeping, and head-down (HD) position. Significant changes in flow were observed during the HD position and quit high arterial blood pressure in the internal carotid artery (ICA) aneurysm model was established when compared to the normal ICA model. The velocity increased abruptly during the HD position by more than four times (LICA and RICA) and wall shear stress by four times (LICA) to ten times (RICA). The complex spiral flow and higher pressures prevailing within the dome increase the risk of aneurysm rupture.